Diabetes and Hemoglobin A1c as Risk Factors for Nosocomial Infections in Critically Ill Patients - Eirini Tsakiridou; Demosthenes Makris; Vasiliki Chatzipantazi; Odysseas Vlachos; Grigorios Xidopoulos; Olympia Charalampidou; Georgios Moraitis; Epameinondas Zakynthinos (Critical Care Research and Practice)
Objective. To evaluate whether diabetes mellitus (DM) and hemoglobin A1c (HbA1c) are risk factors for ventilator-associated pneumonia (VAP) and bloodstream infections (BSI) in critically ill patients. Methods. Prospective observational study; patients were recruited from the intensive care unit (ICU) of a general district hospital between 2010 and 2012. Inclusion criteria: ICU hospitalization >72 hours and mechanical ventilation >48 hours. HbA1c was calculated for all participants. DM, HbA1c, and other clinical and laboratory parameters were assessed as risk factors for VAP or BSI in ICU. Results. The overall ICU incidence of VAP and BSI was 26% and 30%, respectively. Enteral feeding OR (95%CI) 6.20 (1.91–20.17; P=0.002) and blood transfusion 3.33 (1.23–9.02; P=0.018) were independent risk factors for VAP. BSI in ICU (P=0.044) and ICU mortality (P=0.038) were significantly increased in diabetics. Independent risk factors for BSI in ICU included BSI on admission 2.45 (1.14–5.29; P=0.022) and stroke on admission2.77 (1.12–6.88; P=0.029). Sepsis 3.34 (1.47–7.58; P=0.004) and parenteral feeding 6.29 (1.59–24.83; P=0.009) were independently associated with ICU mortality. HbA1c ≥ 8.1% presented a significant diagnostic performance in diagnosing repeated BSI in ICU. Conclusion. DM and HbA1c were not associated with increased VAP or BSI frequency. HbA1c was associated with repeated BSI episodes in the ICU.